The Oxford handbook of Qur'anic studies - Shah, Mustafa; Abdel Haleem, M. A. 193X- (Oxford handbooks online Religion, 2020)
'The Oxford Handbook of Qur'anic Studies' is an essential reference and starting point for those with an academic interest in the Qur'an. It offers not only detailed reviews of influential subjects in the field, but also a critical overview of developments in the research discourse. It explores the tradition of Qur'anic exegesis and hermeneutics, making it a comprehensive academic resource for the study of the Qur'an.